Role of Digital Humanities in Identifying the Uniqueness of the Author: A Comparative Study of Stylometric Tools in the Works of Amitav Ghosh - V., Thamil Selvi; P., Ramya (Recent Research Reviews Journal, 2025)
In the era of AI and digitalization, software tool utilization is no longer confined to the discipline of Computer Science and Engineering. Scholarship in the Humanities increasingly demands the use of computational methods for further understanding and interpreting texts. Digital Humanities, or alternatively Humanities Computing, has been a fascinating subject of research for over seven decades. Since it was rebranded as Digital Humanities in 2004, it has undergone radical transformation. The basic purpose of Digital Humanities has shifted from the mere digitization of texts to utilizing computational technology for the complex analysis of traditional and digital texts. Scholars all over the world have utilized many software programs for analyzing large corpora of texts. However, in literature, there is a significant gap in researching the applicability of Digital Humanities tools. A recurring debate in thesis papers is that of the originality of the author. All this can be made easier and more systematic with the right tool at the right time. Most researchers struggle to identify the right tool for their research in literature. The biggest limitation of Digital Humanities is that most of the tools are computer programs, and some knowledge of programming languages is needed. This research aims to bridge this gap by focusing on the installation process, usability, and application of Digital Humanities tools to literature. It seeks to compare two stylometric devices, Stylo and JStylo, which help establish the originality of the author. These devices extrapolate stylometric attributes such as word frequency, sentence length, and lexical richness. They also evaluate the quality of their visualizations, clustering precision, and variance in identifying stylistic trends. The study analyzes the tool best suited to describe the singularity of the writer by contrasting their style with that of contemporary writers. By employing stylistic analysis, intertextuality, and citation mapping, this book probes the potential of Digital Humanities techniques in uncovering new insights into the singularity of authors’ styles.